Pengaruh Penggunaan QRIS dan Literasi Keuangan terhadap Akuntabilitas Laporan Keuangan UMKM di Kota Malang: Peran Mediasi Transparansi - Qorirotul A’iny; Umi Nandiroh; Nur Diana (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Many Micro, Small, and Medium Enterprises (MSMEs) face low accountability in financial reporting due to inconsistent manual recording and a lack of systematic financial statements. This study aims to analyze the effects of digital payment QRIS and financial literacy on the accountability of MSME financial statements in Malang City, while investigating the mediating role of financial statement transparency. The research utilizes a quantitative causal associative approach. Data were collected via questionnaires from active MSME owners who utilize QRIS and maintain business financial records, selected through purposive sampling. The data were analyzed using multiple linear regression and the Sobel test. The results reveal that both digital payment QRIS and financial literacy have a positive and significant effect on financial statement transparency and accountability. Furthermore, transparency significantly influences accountability and successfully serves as a partial mediator in bridging the relationship between both digital payments and financial literacy toward the accountability of MSME financial statements. In conclusion, achieving high accountability requires not only technology and financial knowledge but also a transparent governance process that transforms transaction data into open financial information.